The Role Of Crossbreeding and Hybrids in Selection Work - Normatov Ruzibek Jurakul o’g’li; Bobomurodov Murodjon Khojimurotovich; Normatov Jurabek Abdulla o’g’li; Khamzaev Temur Yigitalievich; Sayfullaev Asror Anvar o’g’li (International Journal on Human-Computing Studies, 2021)
The use of population-created populations using analytical selection is of great benefit to selection. These varieties, in many respects, surpass the original material from which they originated. However, in the selection varieties created as a result of selection of natural populations, some features of the original material are preserved. In most of them, features such as high productivity and disease resistance are low